Peace Education: Pembelajaran Anti Kekerasan dan Relevansinya terhadap Pendidikan Islam - Irawan, Vaesol Wahyu Eka (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Portraits in schools still do not show the ideal ideals of education. Practices of violence often still emerge, not infrequently taking lives. Strategies of learning methods in schools must be conditioned towards peace. Creating an atmosphere as conducive as possible by seeking non-violence to minimize vertical-horizontal conflict. Education is a medium that is quite effective in efforts to transform all forms of study of peace. Through morally-spiritually enlightening education, violence can be prevented. The main foundation of pedagogic peace education is cooperative learning, democratic society, sensitivity to morals, and critical thinking. Furthermore, Islamic education, in this case, is intended to participate in taking part in efforts to minimize the potential for conflict - or even avoid sharp disputes - as a result of the inevitability of meeting global currents. This paper is an alarm ongoing with the real demand that education must develop, metamorphose into a better form.